Predictors of Infection in Children with Systemic Lupus Erythematosus: A Single Center Study in Indonesia - Maria Kristianti Sari MD, MSc; Cahya Dewi Satria MD, MSc; Eggi Arguni MD, MSc, PhD (SAGE Publishing, 2021)
Patients with Systemic Lupus Erythematosus (SLE) are susceptible to infection due to defects in their immune system. Corticosteroids and immunosuppressant drugs used as SLE therapy also contribute to infection. This study aimed is to determine predictors of infection in pediatric patients with SLE. This retrospective cohort study was conducted at Dr. Sardjito Hospital, a referral hospital in Yogyakarta, Indonesia between 2013 and 2019. Logistic regression analysis was performed to identify predictor variables for the occurrence of infection. A total of 109 SLE patients were included in this study. The incidence of infection in children with SLE was 27.5%. The most common types of infection in hospitalized SLE patients were urinary tract infections (41%), skin and soft tissue infections (20.5%), and pneumonia (20.5%). Multivariate regression analysis showed that the use of methylprednisolone pulse dose (RR 3.204; 95% CI 1.234-8.318) was a predictor of infection. Clinician should closely observe SLE patients with predictors for infection.